Age-Related Differences in Physical Abilities in Competitive Sports: A Literature Review - Nimrot Manalu; Dika Rahyandi; Revan Nando Nehe (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: This literature review aims to analyze and synthesize existing research on how physical abilities vary with age among competitive athletes, highlighting developmental trends, performance peaks, and declines. Methods: A systematic search was conducted in databases including PubMed, MDPI, and Sport Science journals, focusing on studies published up to 2025 that examine age-related differences in physical performance in competitive sports. Inclusion criteria encompassed studies assessing anthropometric, physiological, and skill-based parameters across different age groups. Results: Findings consistently show that physical abilities such as speed, agility, strength, and endurance improve from childhood through adolescence, peak in early adulthood, and decline progressively with aging. Technical skills and cognitive factors increasingly influence performance in older athletes. The relative age effect also impacts youth performance assessments. Conclusion: Age significantly affects physical abilities in competitive sports, with distinct developmental phases requiring tailored training approaches. Understanding these differences is essential for talent identification, training optimization, and injury prevention.